20‐HETE synthesis inhibition attenuates traumatic brain injury–induced mitochondrial dysfunction and neuronal apoptosis via the SIRT1/PGC‐1α pathway: A translational study. (13th December 2020) - Cui, Wenxing; Wu, Xun; Shi, Yingwu; Guo, Wei; Luo, Jianing; Liu, Haixiao; Zheng, Longlong; Du, Yong; Wang, Ping; Wang, Qiang; Feng, Dayun; Ge, Shunnan; et al.
Abstract: Objectives: 20‐hydroxyeicosatetraenoic acid (20‐HETE) is a metabolite of arachidonic acid catalysed by cytochrome P450 enzymes and plays an important role in cell death and proliferation. We hypothesized that 20‐HETE synthesis inhibition may have protective effects in traumatic brain injury (TBI) and investigated possible underlying molecular mechanisms. Materials and methods: Neurologic deficits, and lesion volume, reactive oxygen species (ROS) levels and cell death as assessed using immunofluorescence staining, transmission electron microscopy and Western blotting were used to determine post‐TBI effects of HET0016, an inhibitor of 20‐HETE synthesis, and their underlying mechanisms. Results: The level of 20‐HETE was found to be increased significantly after TBI in mice. 20‐HETE synthesis inhibition reduced neuronal apoptosis, ROS production and damage to mitochondrial structures after TBI. Mechanistically, HET0016 decreased the Drp1 level and increased the expression of Mfn1 and Mfn2 after TBI, indicating a reversal of the abnormal post‐TBI mitochondrial dynamics. HET0016 also promoted the restoration of SIRT1 and PGC‐1α in vivo, and a SIRT1 activator (SRT1720) reversed the downregulation of SIRT1 and PGC‐1α and the abnormal mitochondrial dynamics induced by 20‐HETE in vitro. Furthermore, plasma 20‐HETE levels were found to be higher in TBI patients with unfavourable neurological outcomes and were correlated with the GOS score. Conclusions: The inhibition of 20‐HETE synthesis represents a novel strategy to mitigate TBI‐induced mitochondrial dysfunction and neuronal apoptosis by regulating the SIRT1/PGC‐1α pathway. Abstract : The mechanism on 20‐HETE–induced alterations of mitochondrial dynamics in neurons. 20‐HETE is synthesized from AA by CYP4A, which is inhibited by HET0016. The alterations of mitochondrial dynamics induced by 20‐HETE activate oxidative stress and subsequently result in neuronal apoptosis mediated by inhibition of the Sirt1/PGC‐1α signalling pathway.